Two Generalized Lower Bounds for the Circumference - Koulakzian, Mossine S.; Nikoghosyan, Zhora G. (Mathematical Problems of Computer Science, 2021)
In 2013, the second author obtained two lower bounds for the length of a longest cycle C in a graph G in terms of the length of a longest path (a longest cycle) in G¡C and the minimum degree of G (Zh.G. Nikoghosyan, "Advanced Lower Bounds for the Circumference", Graphs and Combinatorics 29, pp. 1531-1541, 2013). In this paper we present two analogous bounds based on the average of the ¯rst i smallest degrees in G ¡ C for appropriate i instead of the minimum degree